MENGEMBANGKAN FISIK MOTORIK HALUS ANAK USIA DINI MELALUI KEGIATAN MEMBATIK DI RA ISLAMIYAH TRIWUNG KIDUL - Amanatul Rufi'ah; Prasetiya, Benny (Al-ATHFAL: Jurnal Pendidikan Anak, 2023)
Fine motor skills are the ability to organize real movements that only cover certain parts of the body and are carried out by small muscles, such as fingers and precise movements of the wrist. One of the movements that can be implemented to develop children's fine coordination skills is batik activities to develop the fine motor skills of young children. RA Islamiyah Triwung Kidul will be the place for this research, which is undertaking develop fine motor physical abilities in early childhood through batik activities. The importance of physical development of fine motor skills at the beginning of early childhood development is the basis for the formulation of this research. Fine motor physical abilities in early childhood education are still lacking, especially in pre-writing tasks such as holding a pencil that is still stiff and tracing it, and coloring that still has streaks on it. Basic batik projects can help improve fine motor skills. Methodology This research uses qualitative research methods. We call this kind of research descriptive research. and describes real-world events taking information from documents, interviews, and observations. The research conclusion shows that even a simple batik project can improve the fine motor physical abilities of young children. Key words : Batik, Early Childhood,  Fine Motor Skills.